Distribution of Posidonia oceanica (L.) Delile meadows around Lampedusa Island (Strait of Sicily, Italy). Issue 1 (4th November 2016) - Tonielli, Renato; Innangi, Sara; Budillon, Francesca; Di Martino, Gabriella; Felsani, Marcello; Giardina, Fabio; Innangi, Michele; Filiciotto, Francesco
ABSTRACT: We present a seabed map around Lampedusa, the largest island of the Pelagie Islands Marine Protected Area (Italy, western Mediterranean). The seafloor was mapped using bathymetry and backscatter multibeam systems along with an underwater camera for direct observations and ground truthing, from the coastal area to about 50 m depth. The map was produced to monitor the present-day distribution of the Posidonia oceanica meadows around the Island. P. oceanica is the most important endemic seagrass species of the Mediterranean Sea and it can form meadows or beds extending from the surface to 40–45 m depth. These meadows provide habitat for a large marine community, thus increasing biodiversity of the coastal zone, stabilizing sediments and reducing coastline erosion. The seagrass meadows are susceptible to regression in response to specific impacts, thus their presence and abundance is an indicator of the overall environmental quality of the coastal zone. Recently, within the Marine Strategy Framework Directive (2008/56/EC), P. oceanica has been selected as an indicator of the Good Environmental Status for marine areas. Consequently, the Pelagie Islands Marine Protected Area launched a project to assess the conservation status and map the distribution of P. oceanica meadows. The resulting 1:15, 000 scale map includes information about the Mediterranean seagrass and the distribution of five acoustic facies reflecting hard lithologies and soft substrates. The Lampedusa seabed map provides new information, which contributes to the development of a detailed benthic habitat map and a more comprehensive maritime spatial planning of this Marine Protected Area.